Ethnobotanical study of Indigenous Knowledge on Some Wild Plants in Parsa District, Nepal - Singh, Shila (Journal of Natural History Museum, 2018)
The present study was carried out to document ethnobotanical informations of some wild plants used by the Tharu community of Parsa district forest area of Nepal. This study was designed to gather primary folk knowledge on different plant based therapies used at four adjacent villages; Gadi, Madhuban mathwal, Sonbarsa and Shanker Sharaiya for various purposes through frequent field visits in the forest and adjoining villages, participatory observations, group discussion, interviews with tribal's and local knowledgeable people in the year 2013 from February to November. A total of 54 ethno-medicinal wild plant species belonging to 29 families and 44 genera were documented in this study. It can be concluded that Tharu community of the Parsa district possess valuable traditional knowledge on plant based therapies. Present documentation will provide novel information to protect traditional knowledge for the conservation and sustainable use of the rich biodiversity for future generations and serve to open the door for new pharmacological research.  J. Nat. Hist. Mus. Vol. 29, 2015, Page: 103-121